2011
DOI: 10.1089/jmf.2010.0051
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Screening of Several Tomato Extracts

Abstract: The cytotoxic effects of extracts of the tomato variety "Racimo" have been evaluated through the use of the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay at several concentrations. Three extracts-ethanol-water, petroleum ether, and in vitro digested tomato-exhibited in vitro cytotoxicity against the proliferation of the cultured cancer cell line HT-29. The concentration that caused 50% inhibition of cancer cell growth occurred (GI(50)) of the different extracts for HT-29 cells was 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…As expected, the total FAs in all tomato varieties was low, a result which agrees with previous reports, and thus this fact prevents it being considered that such lipids are nutritionally relevant . However, some FAs are important cytotoxic agents against colorectal cancer cells, as previously reported …”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…As expected, the total FAs in all tomato varieties was low, a result which agrees with previous reports, and thus this fact prevents it being considered that such lipids are nutritionally relevant . However, some FAs are important cytotoxic agents against colorectal cancer cells, as previously reported …”
Section: Resultsmentioning
confidence: 58%
“…To check the actions of tomato varieties on colorectal cancer cells viability, cell proliferation and cytotoxicity, fruit extracts were made by using two solvents, ethanol/water (1:1, v/v) and petroleum ether. Polarity differences allows them to extract compounds with a different ranges of solubility; thus, the biological activity of different tomato compounds was discerned depending on their hydrophilic or lipophilic characteristics . 1 H NMR analyses showed that petroleum ether extracts contained a mixture of glycerol FA esters (mainly derived of LA and OA), as well as lycopene and β ‐carotene in minor amounts, whereas the ethanol/water extract was mainly composed of carbohydrates, for instance fructose and glucose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An illustrative example is found in the study of the antiproliferative activity of the in vitro gastrointestinal digest of sea cucumber wall (Pérez-Vega et al 2013 ). Another representative study is found in the assessment of the cytotoxic activity of different extracts from "Racimo" tomato variety and simulated digests against HT29 cell growth, including also the evaluation of the selectivity of the toxic effect against cancer cells (Guil-Guerrero et al 2011 ). Other activities have been widely studied on HT29 cells or derived lines, such as immunomodulatory, antioxidant or barrier protective properties.…”
Section: Functionality Studiesmentioning
confidence: 99%
“…In addition, data from NHANES III indicate that for women 51-70 y, the medians for 50 th & 75 th percentiles of lutein/zeaxanthin intake were 1.7 and 2.4 mg/d, respectively [74]. Foods rich in an acyclic carotenoid, lycopene, one of the most abundant carotenoids in human blood and tissues, has been found to be associated with an inverse risk of cervical [75], prostate [76], and colon [77] cancers.…”
Section: Proposed Biological Functions Of Phytochemicalsmentioning
confidence: 99%